Spanish tax law in the light of female entrepreneurship and gender budgets - Siota ´Alvarez, M´onica (2024)
There is unanimity at all levels and in all social spheres that inequality between women and men is an abnormality that must be eradicated in increasingly inclusive societies. The legal system should not only prohibit discrimination, but should go further and introduce positive and proactive measures for equality and, specifically, for female entrepreneurship. This involves analysing whether tax rules are the best way to directly achieve more female entrepreneurship and, indirectly, to pursue other goals such as professionalisation in the care of dependents or to increase the birth rate. Hence, the perspective of public spending is fundamental to study the impact of these measures and, therefore, their effectiveness. This gender perspective in the public budget makes it possible to analyse, measure and change the policies that are adopted in this area.